基于文化话语的中国-东盟贸 易关系建构 = Construction of China ASEAN Business Relationship under the Framework of Cultural Discourse - Zhoumin, Yuan (Sinología hispánica. China Studies Review, 2015)
基于文化话语的研究理念，本文主要集中 于话语内容与话语主题分析，从东盟（新加坡） 视角和中国视角考察了中国东盟的和谐贸易合 作关系。研究发现，和谐与合作是双方视角下 贸易关系的主题。中国东盟贸易关系呈现逐年 增长的趋势，并且与双方政治话语互动正相关。 东盟方相对于中国使用了较多的竞争性言语行 为。中国政府和企业需要灵活运用贵和尚中的 语用原则，合理安排话语布局， Framed upon the Cultural Discourse Studies, the present literature focuses on the analysis of discourse content and discourse topic, firstly investigating the harmonious business cooperation of China-ASEAN from both the perspective of ASEAN (Singapore) and China is found that the bilateral business relationship is mainly characterized by harmoniousness and cooperation, but ASEAN countries make more use of competitive speech acts. It is claimed that Chinese government and industries have to flexibly employ the pragmatic principle of gui he shang zhong (Valuing Harmony and Esteeming Mean), wisely plan discourse organization, and seek in-depth business development in the mixture context of discourse harmony and conflict.